2019
DOI: 10.3758/s13415-019-00692-5
|View full text |Cite
|
Sign up to set email alerts
|

Neural correlates of reward-related response tendencies in an equiprobable Go/NoGo task

Abstract: Previous research has shown that motivational signals bias action over inaction, which may be due to putative inherent valenceaction mappings, similar to those observed in the emotional domain. In the present functional magnetic resonance imaging (fMRI) study we sought to investigate the neural underpinnings of such reward-related response tendencies, and in particular, how valence-action compatibility effects arising from predominant response tendencies are reflected at the neural level, and whether overlappi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 49 publications
3
23
0
Order By: Relevance
“…Such appetitive classical conditioning is thought to underlie much of everyday human behavior (Bray et al, 2008;Blechert et al, 2016;Cartoni et al, 2016), helping maintain both adaptive and maladaptive behaviors, for example addiction (Hogarth, 2012;Garbusow et al, 2016). A growing number of humansubjects studies have demonstrated the effects of a conditioned cue on attentional bias (Thewissen et al, 2007;Le Pelley et al, 2015Leong et al, 2017), choice (Astur et al, 2015;Vogel et al, 2018;Genauck et al, 2019), response speed (Freeman et al, 2014;Asci et al, 2019) and response frequency Alarcón and Bonardi, 2019). However, the evidence of behavioral invigoration in the presence of conditioned stimuli in humans is less robust compared to a long history in animal experiments.…”
Section: Introductionmentioning
confidence: 99%
“…Such appetitive classical conditioning is thought to underlie much of everyday human behavior (Bray et al, 2008;Blechert et al, 2016;Cartoni et al, 2016), helping maintain both adaptive and maladaptive behaviors, for example addiction (Hogarth, 2012;Garbusow et al, 2016). A growing number of humansubjects studies have demonstrated the effects of a conditioned cue on attentional bias (Thewissen et al, 2007;Le Pelley et al, 2015Leong et al, 2017), choice (Astur et al, 2015;Vogel et al, 2018;Genauck et al, 2019), response speed (Freeman et al, 2014;Asci et al, 2019) and response frequency Alarcón and Bonardi, 2019). However, the evidence of behavioral invigoration in the presence of conditioned stimuli in humans is less robust compared to a long history in animal experiments.…”
Section: Introductionmentioning
confidence: 99%
“…Searches were limited to human participants, published in English, and between years 1978 and 2020. The reference list of each identified paper was examined for any eligible articles not identified through our search strategy, and this led to the addition of one further article (Asci et al, 2019).…”
Section: Search Strategymentioning
confidence: 99%
“…Second, motivated by specific assumptions about neural interactions between motivation and cognitive control and limited by technical constraints of DCM, we only included a small number of brain regions in the DCM analysis thereby neglecting other areas presumably involved in motivated control, for instance, the ventral striatum (Aarts et al, 2011; Asci, Braem, Park, Boehler, & Krebs, 2019; Cools, 2008). Note, however, that effective connectivity does not reflect anatomical connectivity.…”
Section: Limitationsmentioning
confidence: 99%